1999
DOI: 10.1128/aem.65.9.4126-4133.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Nitrite-Oxidizing Bacteria with Monoclonal Antibodies Recognizing the Nitrite Oxidoreductase

Abstract: Immunoblot analyses performed with three monoclonal antibodies (MAbs) that recognized the nitrite oxidoreductase (NOR) of the genus Nitrobacter were used for taxonomic investigations of nitrite oxidizers. We found that these MAbs were able to detect the nitrite-oxidizing systems (NOS) of the generaNitrospira, Nitrococcus, andNitrospina. The MAb designated Hyb 153-2, which recognized the α subunit of the NOR (α-NOR), was specific for species belonging to the genus Nitrobacter. In contrast, Hyb 153-3, which reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 37 publications
2
44
0
Order By: Relevance
“…In fact, the two guilds almost always coexist in WWTPs, although Nitrospira spp. are most prevalent during periods of optimal performance (Bartosch et al, 1999;Wagner et al, 2002), particularly Type I and Type II Nitrospira sublineages (Daims et al, 2001). It is reported here that unstable behaviour in nitrification can result from occasional, but sometimes dramatic shifts in the NOB guild, which can cause sudden and complete loss of function.…”
Section: Introductionmentioning
confidence: 60%
“…In fact, the two guilds almost always coexist in WWTPs, although Nitrospira spp. are most prevalent during periods of optimal performance (Bartosch et al, 1999;Wagner et al, 2002), particularly Type I and Type II Nitrospira sublineages (Daims et al, 2001). It is reported here that unstable behaviour in nitrification can result from occasional, but sometimes dramatic shifts in the NOB guild, which can cause sudden and complete loss of function.…”
Section: Introductionmentioning
confidence: 60%
“…Therefore, the physiological and biochemical properties of NOB have been characterized by observations of Nitrobacter strains (Starkenburg et al, 2011). More recently, cultivation-independent molecular methods (Wagner et al, 1996;Burrell et al, 1998;Hovanec et al, 1998;Juretschko et al, 1998) and immunological techniques (Bartosch et al, 1999) have indicated that the genus Nitrospira is more widespread than Nitrobacter and most likely plays a primary role in the global nitrogen cycle, and natural nitrite conversion is an important part of the global nitrogen cycle. The genus Nitrospira represents a monophyletic lineage within the deep-branching bacterial phylum Nitrospirae, which is distinct from that of proteobacterial NOB (Ehrich et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The identification and monitoring of microorganisms and bioanalytes from complex natural samples is of general interest in biomedical, bioterrorism, environmental, industrial or astrobiological applications (Schloter et al, 1995;Luppa et al, 2001;Lim et al, 2005;Parro et al, 2008;Van Dorst et al, 2010). For environmental applications, immunoassays have been developed for identification of organisms, detection of key metabolic enzymes and serotyping bacterial pathogens (Bartosch et al, 1999;Fiencke and Bock, 2004;Marimon et al, 2010). O'Connor and Coates (2002) reported a good example of the usefulness of immunoassays for the description of physiological functionality of complex microbial populations regardless of their phylogenetic affiliations: they developed a universal immunoprobe for (per)chlorate-reducing bacteria by producing antibodies against the key enzyme for (per)chlorate reduction (chlorite dismutase).…”
Section: Introductionmentioning
confidence: 99%